Alone as effective as together: AMF and Trichoderma inoculation boost maize performance but differentially shape soil and rhizosphere microbiota - Fernandez Gnecco, Gabriela Amancay (2024)
he objective of the present study wasto evaluate the effects of single or combined inoculation of Trichoderma harzianum,strain TGFG411, and a consortium of arbuscular mycorrhizal fungi (AMF) on plantgrowth, and native microbial communities (here bacteria/archaea, fungi and AMF) inroot‐associated soil (RAS) and rhizosphere (RH), that is, soil loosely or tightly attached tothe roots, respectively.Materials and Methods: A greenhouse experiment was carried out with non‐sterileagricultural soil and the model crop maize, which was single inoculated with eitherTGFG411 or AMF or received a combined inoculation of TGFG411 + AMF. Controlplants received only water. Seven weeks after the second AMF inoculation, the plantgrowth promotion capacity of the inoculants was measured based on shoot and rootparameters. Furthermore, RAS and RH microbiota (fungi including AMF, bacteria andarchaea) were assessed via a combination of different cultivation‐dependent,microscopic and DNA‐based methods.Results: After 7 weeks of maize growth, both single and combined inoculation of AMFand TGFG411 enhanced shoot dry weight and led to a significant reduction in rootbiomass. The TGFG411 strain successfully established in the soil. However, no definiteevidence for the establishment of the inoculated AMF was found. Single or combinedinoculation of TGFG411 and AMF modified the composition of total bacterial in the RH,whereas modulated total fungal communities in the RAS.Conclusion: The combined inoculation did not result in a significant improvement ofplant performance compared with single inoculation likely due to optimal nutrientsupply. However, samples receiving the combined inoculation exhibited a distinct modulation of the native RAS/RH microbiota, which may influence the inoculantefficacy under less favourable conditions.